Predicting Protein–Protein Interactions Between Rice and Blast Fungus Using Structure-Based Approaches - Zheng, Cunjian; Liu, Yuan; Sun, Fangnan; Zhao, Lingxia; Zhang, Lida (Frontiers in Plant Science, 2021)
Rice blast, caused by the fungus Magnaporthe oryzae, is the most devastating disease affecting rice production. Identification of protein-protein interactions (PPIs) is a critical step towards understanding the molecular mechanisms underlying resistance to blast fungus in rice. Here, we presented a computational framework for predicting plant-pathogen PPIs from structural evidences. Compared with the sequence-based methods, the structure-based approach showed to be more powerful in discovering new PPIs between plants and pathogens. Using the structure-based method, we generated a global PPI network consisted of 2018 interacting protein pairs involving 1344 rice proteins and 418 blast fungus proteins. Network analysis showed that blast-resistance genes were enriched in the PPI network. The high predictability of the PPI network enabled systematic discovery of new blast-resistance genes using guilt-by-association. The network provided a global map to help accelerate identification of blast-resistance genes and advance our understanding of plant-pathogen interactions.